Eksplorasi Dimensi Kecerdasan Emosional Dan Spiritual Dalam Fikih Shalat : Studi Pengembangan Materi Bahan Ajar Dan Strategi Pembelajaran - Nanang Abdillah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Learning materials are not merely tools, but rather as the main source that provides important substance for learning. This concept is enriched by the view that learning materials are not only physical materials, but also something that carries meaningful messages to achieve teaching goals. Learning material on prayer jurisprudence, it can be seen that there is a gap in the approach which is still focused on declarative and procedural aspects. These materials do not yet reflect comprehensive Islamic education that can penetrate the emotional and spiritual dimensions. Therefore, there is a need to develop more meaningful prayer fiqh material by combining emotional and spiritual values ​​as additional material to support the goals of Islamic education that are in accordance with the principles of Islamic education. religious principles and Education laws. The emotional and spiritual intelligence material is prepared first according to the content of prayer jurisprudence. Ari Ginanjar's ESQ concept can be used as the main reference for this preparation. The results of the preparation are combined with existing prayer jurisprudence material. The results of this combination are then said to be the development of teaching materials, for example; The material on prayer intentions is given additional material on spiritual emotional intelligence which explains that intention contains the meaning that "Integrity is sincerity, honesty and commitment that grows from the impulse of one's conscience, not influenced by other factors". After the development of the teaching materials was ready, inquiry, contextual and expository learning strategies were chosen as relatively easier strategies in interpreting prayer fikh material based on the development of emotional and spiritual intelligence material.